History and His-Story in André Malraux's La Corde et les souris - Lawrence D. Kritzman (Studies in 20th & 21st Century Literature, 1985)
In La Corde et Ies souris Malraux attempts to overcome human transience and mortality by memorializing the ephemeral through the artifice of writing. The rhetoric of the self-portrait takes the form of a historical narrative in which the relationship of history to memory as textual archive affords the Malrucian subject a "reprieve" by effacing the inherent status of contingency. The text thus becomes a veritable cultural mausoleum that sublates the implicit negation of death and allows the author to become more than a conscience without memory.
Keywords: La Corde et Ies souris; Malraux; human transience; mortality; memorializing; ephemeral; self-portrait; Malrucian subject; contingency; death; author